Range of use, nativisation and acceptability in Malaysian English - Wahid, Ridwan (IIUM Press, 2016)
Malaysian English grammar is claimed to contain localised, non-standard features that exist alongside exonormative counterparts. Taking diffusion of such features as an indicator of nativisation, this study argues that this process is influenced not by proficiency and language use alone, but also by the uses to which the language is put, i.e. range of use. One way to prove this is to measure diffusion of features among proficient speakers whose ranges of use vary considerably. In this paper, I present findings from a survey of acceptability of 11 deviant grammatical features adapted from Bautista (2004) and 28 divided usages adapted from Lee and Collins (2006). Comparing two groups of proficient speakers – one of wide range users, and the other of non-wide range ones – the study found that the wide range users tended to have more liberal attitudes towards non-standard grammatical features than their non-wide range counterparts. Given the high acceptability levels shown by these acrolectal speakers in formal contexts, the findings suggest that such speakers bear some influence on the nativisation of these features as well as their pathways to standardisation.